Leksikon dalam Aktivitas Pertanian Masyarakat Yogyakarta - Ridha Mashudi Wibowo (SASDAYA: Gadjah Mada Journal of Humanities, 2020)
This research aims to document linguistic category regarding the field of agriculture, from the perspective of society in association with plants and their environment, the elaboration of local wisdom in viewing plants and their environment regarding agriculture as part of their livelihood. The ethnobiology lexicon data and other information in relation to plants in Javanese are compiled in articles, books, and dictionaries along with several native speakers of Javanese who reside in the southern part of DIY. Verbal source of data is obtained by controlled elicitation method and analyzed with component analysis method as well as introspection. The result demonstrates the inventorizing of agricultural terms which encompass words, abbreviation, coinage either monomorphemic or polymorphemic. The variety of agricultural term is used in the society in categorizing plants and their environment and highly regarded local wisdom perspective by the people amidst the emergence of renewal in agriculture. This research contributes to the study of language in agricultural activities in Javanese society, especially Yogyakarta in the perspective of ethnics, especially in the formation of language terms which at some level have become a new identity adopted into Javanese. It is hoped that the results of this study can be used by the wider community in using the agricultural lexicon in accordance with the times without forgetting the preservation of the agricultural lexicon that is part of its local wisdom.agriculture, local wisdom, lexicon.